Monoclinic form of isopentenyl diphosphate isomerase: a case of polymorphism in biomolecular crystals - de Ruyck, Jérôme (International Union of Crystallography, 2008)
Type 1 isopentenyl diphosphate isomerase (IDI-1) has been crystallized in a new crystal form. After data collection from small thin needle-shaped crystals, a new monoclinic form of the studied protein was identified. In this article, the three crystal forms of IDI-1 (orthorhombic, monoclinic and trigonal) are compared.